Synthesis of gold nanoparticles by block copolymer technique for plasmonic organic photovoltaics - Venkata Kameshwar Rao, Irukuvarjula (2016)
ABSTRACT The present day fossil fuels reserves are depleting with the advent of time. At this juncture, it becomes highly important to find an alternative source of energy to cater the world’s ever growing problem of energy. In this aspect the solar energy through photovoltaic conversion is the most promising candidate for the long run energy generation. Intense research is being done in photovoltaics to reduce the cost of electricity generation using different materials with varying efficiencies. Thin film photovoltaic based on solution processable organic semiconductor offer a distinct advantage compared to its inorganic counterpart. Specifically they are light weight, flexible, solution processable, printable into sheets which enhances ease of mass production. etc. Added to this the power conversion efficiencies are exceeding above 10% on the device scale, paving the way from laboratory to mass production. Furthermore, utilising low band gap materials for enhancing absorption, new device architecture, replacing with newer contact materials to reduce the series resistance, use of various additives, doping of the active layer, utilising various light trapping techniques are done to enhance the efficiencies of these devices. The light trapping in the form of plasmonic structures to increase device performance is being explored in this work. A novel method of pattering the plasmonic structures, block copolymer technique is introduced. The obtained structures are inserted into the plasmonic organic photovoltaics. This is done to capture the far-field scattering and near-field light coupling to increase light absorption and exciton/charge generation, thereby resulting in an improved current density. The key to design and improvement lies in the ability to deeply understand the charge transfer dynamics; ultrafast technique like transient absorption spectroscopy (TAS) is used in this regard. We aim to fabricate periodic nanostructures using block copolymer technique. Gold nanoparticles are synthesised by the reduction of PS4-b-P2VP block copolymer loaded gold chloride using a reactive ion etching. Atomic force microscopy was used to observe the micelles, gold loaded micelles and gold nanoparticles formed on the surface. The sizes of the obtained nanoparticles are in the range from 5-50 nm and the occurrence of the absorption peak at 530 nm for the presence of the gold. Gold plasmonic P3HT: PCBM organic photovoltaic devices made with these nanoparticles, display lower power conversion efficiency compared to the standard device. Transient absorption study of plasmonic devices shows the similar charge transfer dynamics as with the standard sample. FDTD simulation of these Au nanoparticles revealed higher absorption cross-section compared to scattering from 15 nm to 70 nm sizes, leading to absorption of incoming light by nanoparticles and hence lower absorbance by active layer that results in poor plasmonic device performance (lower Jsc). As a further extension of this work, silver nanoparticles of varying size and spacing are simulated. In this plasmonic structure, absorption cross section is found to be dominating the scattering within 10 - 30 nm particle size. The increased absorption is used for near field light coupling and an inverted OPVs device structure is proposed for improving the Jsc. On further increasing the particle size from 50 - 70 nm, the scattering cross-section is found to be dominating the absorption. This mechanism is used for far field light scattering and correspondingly for increased current density of devices.